2010
DOI: 10.1007/s10067-010-1398-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity, reliability, and comparison of the WOMAC osteoarthritis index and Lequesne algofunctional index in Turkish patients with hip or knee osteoarthritis

Abstract: To assess validity and reliability of the Western Ontario and McMaster Universities (WOMAC) osteoarthritis (OA) index and Lequesne algofunctional index in Turkish patients with hip or knee OA and to compare the results of the instruments for these two particular sites of involvement. Two disease-specific instruments: WOMAC LK 3.1 and Lequesne indices were administered to 117 outpatients with OA (44 hip and 73 knee) living in Turkey. These indices were administered twice 7-10 days apart to ensure the test-retes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
1
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 17 publications
4
69
1
10
Order By: Relevance
“…Similar studies demonstrated serious disability in their study populations with total Lequesne scores that ranged from 10.51 to 13.67 (11,14,17,18). In our study, the worst score for the Lequesne index was in the ADL domain; this was also reported in the study by Konstantinidis et al (11).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar studies demonstrated serious disability in their study populations with total Lequesne scores that ranged from 10.51 to 13.67 (11,14,17,18). In our study, the worst score for the Lequesne index was in the ADL domain; this was also reported in the study by Konstantinidis et al (11).…”
Section: Resultssupporting
confidence: 89%
“…In our study, the worst score for the Lequesne index was in the ADL domain; this was also reported in the study by Konstantinidis et al (11). However, in the studies by Basaran et al (18) and Nadrian et al (17), the pain domain showed the worst score. After rehabilitation, statistically significant improvements were observed in all domains of the Lequesne index.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations